NETIZENS' INTERACTIONS AND PERCEPTIONS OF YOUTUBE VIDEOS “PANDJI'S MESSAGE TO THE PRESIDENT AND JOKOWI'S POLITICAL DYNASTY” - Khairul Subhan Basri; Iskandar; Nurhakki; Muhammad Qadaruddin (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2026)
Abstract : The phenomenon of political communication in Indonesia shows that YouTube functions not only as a medium for disseminating information but also as an arena for shaping public perceptions regarding issues of power, democracy, and political figures. This study examines political narratives and netizens’ responses to a YouTube video titled “Pandji’s Message to the President and Jokowi’s Political Dynasty,” which was uploaded to the Bocor Alus Politik podcast. The objective of this study is to analyze how the political messages in the video are received, interpreted, and responded to by the audience through comments, replies, sentiment analysis, toxicity, emojis, and semantic clustering. The research approach employs a qualitative method based on Social Network Analysis (SNA) grounded in Stuart Hall’s Reception Theory. Primary data was obtained from 3,592 YouTube comments, while secondary data was sourced from literature on digital political communication. Data collection and analysis were conducted using Communalytic.org, supported by VADER, TextBlob, word clouds, emoji clouds, semantic graphs, and toxicity analysis. The results indicate that the video generated a high level of digital engagement, particularly during the initial upload period, with a dominance of replies signaling active interaction among netizens. Comment sentiment was largely neutral, followed by positive comments indicating acceptance of Pandji’s criticism, while negative comments were relatively few. Toxicity levels were low, resulting in reflective discussions with minimal aggression. Semantic clustering yielded 65 main clusters and 1,452 outliers, indicating diverse interpretations of issues related to the political dynasty, Jokowi, Pandji, and democracy. These findings confirm that the digital audience is active in decoding messages, making YouTube a space for the negotiation of meaning, political expression, and the formation of public opinion. Practically, the results of this study provide benefits for researchers, the media, and content creators in understanding the dynamics of critical, participatory, and controlled digital political conversations, while also serving as a reference for effective political communication strategies in the social media era